Scaling-up of the electrochemical leaf system - Cheng, B (2022)
This thesis presents an exploration of the Electrochemical Leaf (e-Leaf) with a novel application-oriented direction. The e-Leaf, a recent breakthrough made in the Armstrong group in the area of bio-electrochemical catalysis, is inspired by the natural leaf: enzyme cascade is immobilised in the nanopores of the electrode, allowing multi-step biotransformations to be energised, controlled, and monitored in real time. Ferredoxin NADP+ reductase (FNR) is the key enzyme in the e-Leaf, catalysing the interconversion of NADP+/NADP(H). Other co-entrapped NADP(H)-dependent enzyme(s) catalyse reactions coupled to this regeneration, achieving a fast conversion due to the very high effective concentration of enzymes and short distances for cofactor and reactants to diffuse between the enzymes in the nanopores. The e-Leaf is a powerful tool for the investigation of biocatalytic processes and potentially for the production of valuable chemicals.